LOSARI BEACH TOURISM DEVELOPMENT EFFORTS IN MAKASSAR CITY VIEWED FROM REVISIT INTENTION ASPECT (International Conference on Social and Islamic Studies, 2022)
The Losari Beach area is one of the tourist attractions in South Sulawesi which is located in Makassar City. Tourism industry destinations can provide Regional Original Income (PAD) for Makassar City. Losar Beach has a lot of potential to be utilized, namely as a marine tourism destination, water sports, ports, seafood, shopping places, etc. The purpose of this research is to develop the potential of the city of Makassar as a tourist city, especially the Losar beach area with the aim of reviewing it. This study used a descriptive approach with qualitative descriptive data analysis techniques. Regarding the results of the discussion, namely the current aspects of the development of the Losari beach area, hierarchically this area has enough potential to be developed, especially in terms of spatial patterns so that it can become a world city. At present efforts are being made to integrate other cultural tourism such as Fort Rotterdam with Losari Beach by increasing pedestrian paths so that tourists, both domestic and foreign, can enjoy nature tourism and cultural tourism. Likewise with the area integration efforts that connect the SombaOpu road with Losari beach. In this area, temporary anticipation is being carried out in various supporting institutions related to tourism in the Integrated Business Center area. This achievement must of course be supported by the improvement of various related facilities and infrastructure, such as the provision of inter-city public transportation with direct access to Losari Beach, parking areas around the Losar Beach area, cultural reorganization. Regional regulations and regional regulations and associations have contributed to efforts to develop losari beach tourism through Revisit Intention. The results of the summary of the researcher's notes obtained from secondary data, namely the city government's efforts to evaluate the improvement of Losari beach as a landmark of Makassar city.